Frontiers in 19th-century northern Nigeria†: Les frontières dans le Nigeria du Nord au XIXème siècle. Issue 1 (2nd January 2016) - Last, Murray
Abstract : This essay offers the ethnographic rationale for the original use of the term 'deep-rural' that Chuck Jędrej later adopted for the community he studied in the Ingessana Hills. In Hausaland (northern Nigeria), I use 'deep-rural' to denote the distinctive ecological and sociopolitical context of areas that are very marginal to the core of a centralized Muslim state. Such areas are out of everyday reach of the central government yet not entirely beyond the frontier, and as such offered places of security and escape for radical Muslim as well as non-Muslim groups over the last two centuries. The subcultures that developed there were often innovative and diverse as well as tolerant of difference, in contrast to the conventional, dominant culture of the capital city and its hinterland towns and villages.